The effect of posterior percutaneous endoscopic cervical discectomy vs. percutaneous nucleoplasty in patients with cervical radicular pain due to a single-level contained soft-disc herniation: a retrospective cohort study - Jun Hu; Zi Wang; Yuyu Guo; Liuhu Han; Liyang Chen; Likui Wang (BMC Anesthesiology)
Abstract Introduction Cervical radicular pain (CRP) is a common disorder among adults. Minimally invasive surgical techniques, such as posterior percutaneous endoscopic cervical discectomy (PPECD) and percutaneous cervical nucleoplasty (PCN) are considered when conservative treatment fails to contain severe persistent pain. Our retrospective study evaluated the clinical outcomes of CRP in patients treated with PPECD and PCN. Methods Between May 2019 and June 2021, 67 patients with CRP, due to single-level contained soft-disc herniation, were treated with either PPECD or PCN. Clinical outcomes were assessed by the numerical rating scale (NRS), Neck Disability Index (NDI), and modified Macnab criteria. Pre- and postoperative clinical parameters were also compared. Results Compared with the preoperative values, the mean NRS scores for radicular arm pain and NDI score improved significantly with both treatments. According to the Macnab criteria, patients with PPECD (82.9%) had a higher clinical success rate than patients with PCN (75.0%), however, this difference was not statistically significant (P = 0.5508). No major complications were observed in any patients. Conclusions Both PPECD and PCN are effective and safe options for CRP patients with persistent, and severe pain. Given the absence of superiority in pain relief and clinical outcomes with PPECD, we suggest that the shorter operation time and the less invasive features of PCN is an alternative to PPECD in patients with single-level contained soft-disc herniation. Clinical trial number Not applicable.